Analisis Perilaku Individu dalam melakukan Komunikasi Intrapersona - Wahyu Sudarmawan; Muhammad Rashif Darmawan (Jurnal Ilmu Komunikasi AKRAB, 2026)
Intrapersonal communication is the form of internal communication towards an own personeither conscious or under concious, within which subject communicate with itself or isproposed to define, defend or even develop social, psychological and or self matterphysically. The study is to describe intrapersonal communication behaviour within theframework of self evaluation. Survey was conducted amongst 113 respondents withdescriptive analisys being held for conclusion. The result conclude the importance of internalcommunication to enable individuals to enhance their soft skill simultaneously.